PSIKOSIS PADA REMAJA (USIA SEKOLAH) STUDI KASUS PENDERITA GANGGUAN KEJIWAAN PERSPEKTIF KONSELING KELUARGA - Alfin Siregar (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This paper aims to test a case of people with psychosis in adolescents (school age) and parenting by parents of patients. The method used in this paper uses a qualitative approach with a case study method with instrumental models. The location of this study is located in the Pematang Siantar city, North Sumatra. Researchers in this context tried to reveal the existence of interventions carried out by parents of adolescents to psychiatric disorders. This is based on the scope of family counseling material that the family (parents) has a large role in the emergence of psychiatric disorders in children caused by a homeo-statis. of family life. As a result, researchers found that the main source that causes psychiatric disorders experienced by children is caused by parenting parents in an authoritarian way and tends to lead to acts of violence, so that the space for victimization is limited and has an impact on depression to psychiatric disorders.Key words: Psyshotic disorder, parenting, and family counseling.